PERANCANGAN PASAR ANGSAU - Pamungkas, Gaguk Putra; Hartono, Rudi (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
Markets are social and infrastructure where businesses buy and sell goods, services, and labor. The existing condition of the site located on Jalan A. Yani, Angsau Village, Pelaihari District, Pelaihari City are as follows: Site Position : Hook/Corner, Site Area: 8,375 m2, Soil Type: Hard Soil, Topography: Flat, Site Orientation: West , Vegetation: Trees, Coconut Trees, Cassava Trees, Bamboo Trees, Weeds, Undergrowth, Weeds, and other plants, Drainage: Artificial, Electrical Networks: Overhead, Site Boundaries: - South: Gas Station - West: Road and Mosque - North: Rifle Company - East: Housing. The position of the site which is near the main road roundabout is a strategic position because it is on a street corner which makes its position open from several directions so that it is very precise and ideal as a business or business area.